Bonjours j'ai cette exercice la a faire :

A(t)= (3t+1) au carré - (4t-1) au carré

B(t)= 9(t+1) au carré -4(2t + 3) au carré

C(t)= t au carré + 2t + 1 +(t+1) (3t-5)

D(t)= (2t + 1) au carré + 4t au carré - 1

Merci beaucoup d'avance

1

Réponses

  • Utilisateur Brainly
2013-09-22T13:38:36+02:00
A(t)= (3t+1) au carré - (4t-1) au carré  
      =9t²+6t+1-16t²+8t-1
      =-7t²+14t

B(t)= 9(t+1) au carré -4(2t + 3) au carré  
     =9(t²+2t+1)-4(4t²+12t+9)
     =9t²+18t+9-16t²-48t-36
     =-7t²-30t-27

C(t)= t au carré + 2t + 1 +(t+1) (3t-5)  
     =t²+2t+1+3t²-5t+3t-5
     =4t²-4

D(t)= (2t + 1) au carré + 4t au carré - 1

     =4t²+4t+1+4t²-1
     =8t²+4t